Fostering Statistical Reasoning and Numeracy Literacy: The Role of Scratch-Based Interactive Multimedia in Seventh-Grade Mathematics - Muhammad Ryan Ramadhan; Megita Dwi Pamungkas; Arifta Nurjanah (Jurnal Pendidikan MIPA, 2026)
Interactive learning multimedia is needed to improve students’ numeracy literacy skills. Based on this, this study aims to analyze the validity, practicality, and effectiveness of interactive learning multimedia assisted by Scratch to improve students’ numeracy literacy skills. Based on this, this study aims to develop and evaluate interactive multimedia learning assisted by Scratch to improve students' numeracy literacy skills. This study used a Research and Development (R&D) method based on the ADDIE model. In this study, the sample comprised 32 students from class VII A at SMP Negeri 2 Temanggung. The Sampling technique used was cluster random sampling. Data collection techniques used questionnaires, interviews, completing test questions, and observations. The novelty of this research lies in the development of interactive multimedia using Scratch, a tool that has not previously been used to improve numeracy literacy skills. The multimedia developed was categorized as very valid, with material validity of 85.64% and media validity of 85.78%. Its practicality was also rated very high, as indicated by student responses of 85.94% and teacher responses of 90%.  The multimedia also proved effective in improving numeracy literacy skills, as indicated by the N-Gain score of 0.5550 (moderate category) and significant differences between pretest and posttest results (t = 9.554, df = 31, p < 0.05). Interactive multimedia learning assisted by Scratch was also found to be very practical, with 85.94% of students responding positively in the student response questionnaire and 90% in the teacher response questionnaire. Thus, it can be concluded that interactive multimedia developed using Scratch is valid, practical, and effective in improving students’ numeracy literacy skills. Keywords: numeracy literacy, interactive multimedia, scratch.